Factors related to type 2 diabetic retinopathy and their clinical application value - Lian, Xue-Nan; Zhu, Ming-Ming (Frontiers in Endocrinology, 2024)
To compare the differences in clinical-related factors between patients with type 2 diabetes (T2DM) and those without diabetic retinopathy (DR) and to explore the risk factors or protective factors affecting DR in T2DM patients. We performed a retrospective analysis of 380 patients with type 2 diabetes admitted to Handan Central Hospital from June 2023 to May 2024. Clinical data collected included baseline characteristics, hematological tests, metabolic indicators, and information on diabetic complications and comorbidities. Our findings identified intervention, neck vascular disease, bilateral lower limb venous thrombosis, high creatinine, high glomerular filtration rate, high chloride, high fasting C-peptide, and high lactate dehydrogenase as risk factors for DR. In contrast, High 2hour postprandial C-peptide is a protective factor for diabetic retinopathy. A logistic regression model was constructed using stepwise regression to predict DR occurrence, achieving an accuracy of 0.80 and an AUC of 0.83.